2018
DOI: 10.1155/2018/2465481
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing for Gene Expression Profiles in a Rat Model of Middle Cerebral Artery Occlusion

Abstract: Gene expression regulatory mechanisms in models of middle cerebral artery occlusion (MCAO) have been assessed in some studies, but questions remain. The discovery of differentially expressed genes (DEGs) between MCAO and control rats analyzed by next-generation RNA sequencing is of particular interest. These DEGs may help guide the clinical diagnosis of stroke and facilitate selection of the optimal treatment strategy. Twenty rats were equally divided into control and MCAO groups. Three rats from each group we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Among these genes, Mki67, Top2a, and Cenpf, which are cellular markers for proliferation, were increased in the MCAO model and decreased by EA treatment. This was consistent with previous RNA-seq reports of ischemic stroke (40,41). Previous studies also reported that following ischemic injury, the number of reactive astrocytes increased, and subsequently, microglia were activated since oxidative radical imbalance occurred (41).…”
Section: Discussionsupporting
confidence: 92%
“…Among these genes, Mki67, Top2a, and Cenpf, which are cellular markers for proliferation, were increased in the MCAO model and decreased by EA treatment. This was consistent with previous RNA-seq reports of ischemic stroke (40,41). Previous studies also reported that following ischemic injury, the number of reactive astrocytes increased, and subsequently, microglia were activated since oxidative radical imbalance occurred (41).…”
Section: Discussionsupporting
confidence: 92%
“…Rats were randomly divided into the control (sham surgery) and MCAO groups (n=10 in each group). A focal cerebral ischemia rat model induced by MCAO was established as previously described (19,20). All surgical procedures were performed under anesthesia to minimize animal suffering, according to the National Institutes of Health (NIH) Guide for Animal Care and Welfare (NIH publication no.…”
Section: Methodsmentioning
confidence: 99%
“…There is a need to understand the age-related mechanisms of ischemic injury to improve our ability to discern which therapeutics can be translated from the bench to the bedside 2 . Previous global gene expression studies of experimental stroke using microarrays [27][28][29][30][31][32][33][34] and more recently RNA-Seq [35][36][37] have provided useful insights into the pathophysiology of ischemic stroke and uncovered many altered molecular pathways 38 . However, few studies included aged animals.…”
Section: Introductionmentioning
confidence: 99%